(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
Social networks such as Instagram, Facebook, YouTube, blog, and/or Twitter are already recognized as welcome starting points for influencers ready to start their business. "Influencer" refers to people with intensive activity on social networks, people with many followers but also candidates willing to pay for their influence and to promote some brands. This paper research goal is to determine to what extent the influencers on social networks affect the customers when selecting certain products and services. Within the theoretical background, it is elaborated as follows: (i) the relationship between “influencers” activities and the business sector, (ii) influencers’ domain of affecting the business, (iii) influencers ’mode of doing business, and (iv) the predictions related to “influencers” business model development. The empirical part provides descriptive statistics of the impactinduced within one social network (i.e. Instagram) on the demand for particular products, namely tourist destination. The practical contribution of the paper derives from analysing of one social network „influencing potential” toward a particular market segment, while the academic contribution presents new insights into dynamics between business and influencers as phenomena. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.